An exploratory study on social engagement using Facebook among hotel operators in Malaysia - Fadhil, Nawar Abbood (2016)
The use of social media has changed the way communication and interaction with each other and also with business companies such as how hotel industries take place. Currently, social media is the main tool in hotel industry in facilitating the marketing besides being used in engaging with customers. Indeed, recent studies had discovered that customers make decision largely based on the influence of user-generated content and word of mouth. However, there are limited studies which examined the use of Facebook as a tool to engage with customers especially in Malaysia. Thus, this study aims at exploring the use of social media among Malaysian hotels and how these hotels engage with customers through Facebook. Besides, this study also attempts to identify the metrics used by Malaysian hotels to measure the engagement of their customers. Data were collected through interview and content analysis over the Facebook page of selected hotels. The results had indicated that hotels use Facebook as an important communication tool to engage with their customers in various ways. Besides the benefits, this study also discovered some difficulties faced by the hotels when they communicate socially with their customers. On top of that, this study determined that hotels measure their engagement with customers through Facebook in two ways: (i) using software; and (ii) monitoring the page from inside. The results also had shown that some of the hotels are confused about the way to measure the engagement, in which they only focus on certain metrics while others are neglected. In a nutshell, Facebook pages of Malaysian hotels have a relatively weak engagement with customers especially in voice opinion and advocacy. In contrast, attitude expression has a moderate level.